2010
DOI: 10.1080/10790268.2010.11689702
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender, and Side Differences of Cutaneous Electrical Perceptual Threshold Testing in an Able-Bodied Population

Abstract: Objective: To investigate age, gender, and left-right differences in cutaneous electrical perceptual threshold (EPT) testing in an able-bodied, Australian sample. Study Design: Prospective experimental. Setting: Hospital-based spinal cord injuries unit. Methods: Cutaneous electrical stimulation of the 28 dermatomes at ASIA sensory key points (C2-S4/S5) was performed on 29 female and 16 male healthy volunteers aged 21 to 76 years. Mean EPTs for each dermatome were compared (repeated measures ANOVA) for left-rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
9
22
0
2
Order By: Relevance
“…However, sex differences were not exhibited by analyzing data from males of high body fat percentage and females of low body fat percentage. These results support previous reports , and suggest that body fat percentage affects perception threshold. To explain the relationship between body fat percentage and perception threshold, we considered an anatomical tissue structure under the electrode.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, sex differences were not exhibited by analyzing data from males of high body fat percentage and females of low body fat percentage. These results support previous reports , and suggest that body fat percentage affects perception threshold. To explain the relationship between body fat percentage and perception threshold, we considered an anatomical tissue structure under the electrode.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported sex differences in perception sensitivity for electrical stimulation regardless of electrode type or stimulation site (1,2,(7)(8)(9)11). We observed similar results in this study for all electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An EPT value was considered 'normal' if it was within 2SD of the mean for that dermatome in the gender-adjusted normogram, 11 'abnormal' when it was >2SD of the mean value. As in previous studies, at 10 mA the stimulation was stopped and a lack of response from the subject was noted as an 'absent' EPT value.…”
Section: 11mentioning
confidence: 99%
“…The SD of able-bodied subjects 11 was used to allow for comparison, as the SCI sample size of N = 17 is too small to compute a reliable normogram. EPT changes were assessed over the whole period (1-6 months) and subsequently for the first and second 3-month intervals separately.…”
Section: Evaluation Of Eptsmentioning
confidence: 99%